1989
DOI: 10.1016/s0022-5347(17)39119-x
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Neural Sheath Tumors: Cleveland Clinic Experience

Abstract: Retroperitoneal neural sheath tumors are a rare clinical entity with a variable and nonspecific presentation, whose accurate preoperative diagnosis often can be difficult. Since July 1984, 9 retroperitoneal neural sheath tumors, including 3 benign schwannomas, 3 malignant schwannomas and 3 neurofibromas, were evaluated at our institution. Preoperative evaluation included a computerized tomography scan in all patients and magnetic resonance imaging in 4. Magnetic resonance imaging offered better resolution and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 20 publications
0
20
0
4
Order By: Relevance
“…4 Guz et al also reported that CT-guided biopsy is inaccurate and sometimes misleading. 15 Therefore, surgical operations have been used for pathologic evaluation to enable diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…4 Guz et al also reported that CT-guided biopsy is inaccurate and sometimes misleading. 15 Therefore, surgical operations have been used for pathologic evaluation to enable diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In our case an incisional biopsy provided enough material for a definitive diagnosis complete with immunohistochemical studies. The typical biphasic pattern microscopic features of Schwannomas ( Figure 2 ) coupled with the characteristic areas of degeneration produces the stromal heterogeneity typical of CT and MRI images of Schwannomas.…”
Section: Discussionmentioning
confidence: 97%
“…12 Wide local excision of retroperitoneal schwannomas has been advocated by some surgeons and pathologists who manage these tumours on the basis that malignancy can never be totally excluded. 6,13 However tumour recurrence or malignant transformation almost never occurs in benign schwannomas. [14][15] Provided the diagnosis of a benign schwannoma is established preoperatively, local excision or in difficult cases simple enucleation is adequate as no tumour enlargement has been observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La intervención quirúrgica completa suele ser el tratamiento más correcto, siendo necesaria la extirpación de algunos órganos vecinos en ciertas ocasiones, así como la resección de adecuados márgenes quirúrgicos 1,10 . Posteriormente al tratamiento han sido probados fármacos quimioterápicos sin conseguirse con ello mejoría en la supervivencia 3 .…”
Section: Discussionunclassified